Fungal Agents agents of cutaneous and subcutaneous fungal infections - 5 years experience - Verissimo, Cristina (2019)
Introduction: Fungal infections involving subcutaneous tissue often develop following a penetrating wound through the skin. The etiological agents are usually soil fungi or decomposers of plant material decomposers. Fungal infections involving subcutaneous tissue are frequently grouped as (I) mycetoma (II) chromoblastomycosis which the etiologic agent develops dematiaceous muriform cells in the tissue (III) subcutaneous phaehyphomycosis caused by dematiaceous fungi and (IV) hyalohyphomycosis caused by non dematiaceoushyalin fungi. Mycetoma and chromoblastomycosis are common in subtropical and tropical regions of the world but rare in Europe where subcutaneous infections have a different epidemiology. This work aims to evaluate the epidemiology of cutaneous/subcutaneous infections diagnosed at in our laboratory during a 5 year period.